(3adGM GdSGFd hfLGM GdeSGFds - (3GdWGhSj, GdMSfj, CHh GdbGSe, QVi GdnqOjf, Ydj Hf ehSi Hf LYaQ Hf WGhhS, J (B664 (3g`s ((3eMeO LYaQ Hf eMeO cGXe GdWHGWHGFjs)
(3ChdgG (B:s
(3CMeO Gddg Ld LdGdg HdSGf hLfGf hLhOgeG ef LhO Gdehdi GdeYHhO (B... (3hCYJQa dg HGdefI Ld LdGdg Ydi EWdGb dSGfj HMeOg hYdi JCgjdj ddKfGA Ydi ebOS eLOg(B...s
(3BNQgG (B:s
(3CYhP HeG YGPJ Hg edGFcI Gddg GdebQHhf (B... (3Ke GJad Yf jSGQc KdGKG(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI HQbe(B: 1330s
(3GdCYdGe(B: (3L(B5(3, U(B26s
(3GdPQjYI HQbe(B: 1330s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJUha hGdBOGH GdTQYjIs